2015
DOI: 10.1111/jch.12547
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Oscillometric Blood Pressure Monitoring in Atrial Fibrillation Patients Admitted for Electric Cardioversion

Abstract: The reliability of automated oscillometric blood pressure (BP) monitors in atrial fibrillation (AF) has been poorly investigated, only comparing different patients with AF and sinus rhythm (SR), and is a method influenced by individual characteristics. This study compared the reliability of the oscillometric device A&D TM‐2430 (A&D Company, Tokyo, Japan) with that of a mercury sphygmomanometer in AF patients whose SR was restored after electric cardioversion (ECV). Three consecutive BP measurements were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In our sample all patients suffered from AH. It is known that AH has a higher prevalence in elderly and the prevalence of coincidence of AF and AH increases with age, however, it may be difficult for elderly patients to measure their BP by auscultatory method because of hearing loss or difficulties to fit the cuff properly [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample all patients suffered from AH. It is known that AH has a higher prevalence in elderly and the prevalence of coincidence of AF and AH increases with age, however, it may be difficult for elderly patients to measure their BP by auscultatory method because of hearing loss or difficulties to fit the cuff properly [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Oscillometric method has markedly simplified self–monitoring of BP and it may be a better choice for measuring BP at home [12]. Although oscillometric BP–measuring devices are becoming widespread, they may be considered unreliable for the patients with AF [13] because the devices measure BP from a smooth profile of successive pressure waves [14] and because of high variability of the heart rate and stroke volume during arrhythmia [15]. Furthermore, most automatic BP measuring devices are validated and calibrated only for patients with sinus rhythm (SR) and even manufacturers recommend caution when the devices are used for patients with arrhythmias [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Maselli et al demonstrated that office systolic BP increased significantly (+5 mm Hg) in 63 patients after thirty days from the recovery of SR by ECV, while, on the contrary diastolic BP showed an opposite tendency (−5 mm Hg) . A subsequent study by the same group, in which 54 hypertensive patients underwent ABPM the day before and one month after cardioversion, documented that patients maintaining a SR at follow‐up (n = 34) had significantly higher 24‐hour, nighttime and daytime systolic BP, and significantly lower 24‐hour, daytime, and nighttime diastolic BP .…”
mentioning
confidence: 95%
“…Despite these shortcomings, the findings of Maselli and colleagues do have some relevance to office practice. The mean of three manual BP readings was similar to the oscillometric BP measurements in both atrial fibrillation and sinus rhythm in the same patients.…”
mentioning
confidence: 95%
“…The present study by Maselli and colleagues is unique in that it examines the agreement between manual and oscillometric BP readings recorded in the same patients with and without atrial fibrillation. In this study, manual BP was obtained using a conventional mercury sphygmomanometer and oscillometric readings were taken using a validated oscillometric device (A&D TM‐2430, Tokyo, Japan) designed for 24‐hour ambulatory BP monitoring.…”
mentioning
confidence: 99%